Loss of primary cilia promotes inflammation and carcinogenesis. (25th October 2022) - Paul, Conception; Tang, Ruizhi; Longobardi, Ciro; Lattanzio, Rossano; Eguether, Thibaut; Turali, Hulya; Bremond, Julie; Maurizy, Chloé; Gabola, Monica; Poupeau, Sophie; Turtoi, Andrei; Denicolai, Emilie; et al.
Abstract: Primary cilia (PC) are important signaling hubs, and we here explored their role in colonic pathology. In the colon, PC are mostly present on fibroblasts, and exposure of mice to either chemically induced colitis‐associated colon carcinogenesis (CAC) or dextran sodium sulfate (DSS)‐induced acute colitis decreases PC numbers. We generated conditional knockout mice with reduced numbers of PC on colonic fibroblasts. These mice show increased susceptibility to CAC, as well as DSS‐induced colitis. Secretome and immunohistochemical analyses of DSS‐treated mice display an elevated production of the proinflammatory cytokine IL‐6 in PC‐deficient colons. An inflammatory environment diminishes PC presence in primary fibroblast cultures, which is triggered by IL‐6 as identified by RNA‐seq analysis together with blocking experiments. These findings suggest an activation loop between IL‐6 production and PC loss. An analysis of PC presence on biopsies of patients with ulcerative colitis or colorectal cancer (CRC) reveals decreased numbers of PC on colonic fibroblasts in pathological compared with surrounding normal tissue. Taken together, we provide evidence that a decrease in colonic PC numbers promotes colitis and CRC. Synopsis: Primary cilia are present on colonic fibroblasts and their decrease in number promotes colitis and colon carcinogenesis. In colitis, primary cilia loss appears to be ultimately linked to IL‐6 signaling. Primary cilia (PC) are present on colonic fibroblasts. Induction of either acute colitis or colitis‐associated colon carcinogenesis in mice decreases PC numbers. Primary cilia deficiency promotes colonic pathologies. PC numbers on colonic fibroblasts in biopsies of ulcerative colitis or colorectal cancer patients are decreased. Abstract : Primary cilia are present on colonic fibroblasts and their decrease in number promotes colitis and colon carcinogenesis. In colitis, primary cilia loss appears to be ultimately linked to IL‐6 signaling.